OVERUSE INJURIES IN ADOLESCENT ATHLETES: TRAINING LOAD MODELS, RISK MECHANISMS, AND PREVENTION STRATEGIES - FangJinlin (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Overuse injuries are a major concern in adolescent athletes due to high training volumes, early sport specialization, and ongoing musculoskeletal development. Unlike acute injuries, overuse injuries result from repetitive submaximal loading without adequate recovery, leading to progressive tissue microdamage. This review synthesizes current evidence on training load models, underlying injury mechanisms, and prevention strategies in youth athletes. Key conceptual frameworks including the acute:chronic workload ratio (ACWR), cumulative load theory, and fitness–fatigue model are critically examined. Furthermore, biological, biomechanical, and psychosocial mechanisms contributing to overuse injury development are discussed. Finally, evidence-based prevention strategies including load monitoring, neuromuscular training, and periodization approaches are evaluated. Current evidence suggests that overuse injury risk is multifactorial and cannot be explained by training load alone. Instead, injury emergence results from dynamic interactions between external load, internal capacity, and individual developmental factors. Practical implications emphasize individualized load management and integrated monitoring systems.